Statistical Diagnosis Of The Ict Gap And Teacher Training Adaptability Failure: Validation Of Intervention Urgency In Malaka Regency - Mige, Godlief Erwin Semuel; Tjahjono, Gunadi; Ray, Frans F.G (EDUTEC : Journal of Education And Technology, 2025)
This research aims to statistically diagnose the most pressing teacher competency gaps and evaluate the profound failure of conventional professional development training models in Malaka Regency. Data were collected and analyzed from 50 teacher respondents for descriptive analysis and 68 stakeholders for inferential analysis (One-Way ANOVA). The descriptive results indicate that the need for Information and Communication Technology (ICT) competence, with a mean score of M=4.8, and Inclusive Pedagogy, M=4.5, are at the highest level of urgency, unequivocally signaling critically low digital readiness among educators. Contrasting this urgent need, the existing training programs are perceived by teachers as highly non-adaptive (M=4.3), and the quantifiable real impact on daily teaching practice is assessed as extremely low (M=2.2). The application of inferential statistics through One-Way ANOVA successfully tested the research hypothesis. The analysis validates that fundamental, early-stage intervention focused on foundational skills has a significantly higher level of importance. (M=4.75,p<0.001) when compared to subsequent advanced specialization stages. This statistically robust conclusion provides strong evidence mandating that policymakers must immediately execute a total reform of the training model towards an adaptive scheme, explicitly prioritizing the strengthening of the ICT foundation as the essential catalyst for the success of all future professional development programs. The findings of this research serve as the empirical starting point for developing a comprehensive roadmap for teacher competency improvement in the region.